Institutions and the role of the state - Burlamaqui, Leonardo; Castro, Ana Célia.; Chang, Ha-Joon. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2000)
This book draws together leading scholars in the fields of institutional and evolutionary economics who apply cutting-edge research to one of the most controversial issues of our day, namely, the role of the state.
Includes bibliographical references and index.
rpm 26/08/16
Loans
Keywords: Economic policy; State, The; Institutional economics; Evolutionary economics